An exploration of teaching strategies and methods that contribute to successful outcomes and bring positive change when English is taught as a Foreign Language at tertiary level in Laos - PANMANIVONG , Thavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
As English is becoming a significant language for communication, education, social affairs and economics in Laos, it is essential to ensure that all lecturers/teachers of English use culturally appropriate methods and strategies to help their students reach desirable outcomes. Previous studies have revealed that learning outcomes in English have been unsatisfactory because of lack of motivation, especially for those who study at tertiary level in the Lao People’s Democratic Republic (Lao PDR). Achieving better outcomes from learning English requires high motivation, aspirations and a positive attitude towards learning. However, it remains challenging to foster student motivation and aspiration due to various factors. In this study, semi-structured interviews were conducted with six EFL lecturers from two groups: three lecturers selected as outstanding by the Dean of Education from a public university in Laos, and three Australia Awards Scholars at Flinders University who have taught English at tertiary institutions in Laos. These interviewees provided insights about their experience teaching English and how they dealt with the issues and barriers they faced. They also provided suggestions about how to implement positive change, especially in relation to collaborative professional development for future improvement in EFL teaching and learning. The results demonstrate strategies and methods that the lecturers have applied successfully to motivate their students, as well as to enhance learning outcomes in their professional contexts. Working with other lecturers who have the potential and willingness to make positive changes through professional development and are prepared to apply a variety of teaching strategies and methods in their teaching is a key strategy for success in the Laos context.